1991
DOI: 10.1016/0014-5793(91)81280-l
|View full text |Cite
|
Sign up to set email alerts
|

A novel P‐type ATPase from yeast involved in sodium transport

Abstract: The gene ENA1 was cloned by its ability to complement the Li+ sensitivity of a low Li+‐efflux strain. The nucleotide sequence of the cloned DNA fragment showed that there are two almost identical genes in tandem, and predicts that they encode P‐ATPases. Disruption of both genes originated a strain defective in Na+ and Li+ effluxes, and sensitive to Na+, to Li+ and to alkaline pH. By transformation with ENA1 the defective effluxes and tolerances were repaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
311
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(317 citation statements)
references
References 12 publications
5
311
0
1
Order By: Relevance
“…Two genes for P-type ATPase, PMR1 and PMR2, were cloned by Rudolph et al [1] PMR2 was found later to encode a plasma membrane Na+-ATPase responsible for resistance to high concentrations of Na ÷ and Li + [12][13][14]. It was suggested that PMR1 encodes a Ca2+-ATPase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two genes for P-type ATPase, PMR1 and PMR2, were cloned by Rudolph et al [1] PMR2 was found later to encode a plasma membrane Na+-ATPase responsible for resistance to high concentrations of Na ÷ and Li + [12][13][14]. It was suggested that PMR1 encodes a Ca2+-ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…]?he cells of the pmrl mutant and the WT strain were harvested from the growth medium, washed 4 times with distilled water and resuspended (2x 108 cells/ml) in buffer-glucose solution containing MES/DMG buffer (25 mM, pH 5.0) and glucose (20 mM [1,4], the isogenic pmr2 mutant cells, lacking a cell-membrane Na+-ATPase [12][13][14] and the isogenic WT cells grew well in YPD medium containing 0.3 mM Ca 2+. The growth rate of the pmrl mutant cells was slightly stimulated by the addition of 20 mM Ca ~+ to the medium, markedly inhibited by reducing external Ca 2+ by EGTA, as previously reported [1,4], but was reduced by only 12% (which is no more than the decrease in the growth rate of the WT cells) by increasing strains.…”
Section: '; Measurements Of Ca 2+ Influxmentioning
confidence: 99%
See 1 more Smart Citation
“…This biophysical parameter is determined by the concerted activities of the electrogenic Pma1p H + ATPase and the Trk1,2p K + transporter, which indirectly modulate the uptake of sodium and other toxic cations Goossens et al, 2000). The efflux of Na + from yeast cells is mostly dependent on the Ena1p ATPase (Haro et al, 1991), with the H + -antiporter Nha1p (Prior et al, 1996) and the Snq2p ATPase (Miyahara et al, 1996) playing a secondary role. On the other hand, the H + -antiporter Nhx1p (Nass et al, 1997) catalyses cation accumulation into the vacuole.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation of yeast to these conditions requires the modification of the plasma membrane transport systems to exclude Na + ions from the cytosol and the onset of glycerol synthesis to restore turgor pressure. This adaptation is largely based on changes in the expression of key genes such as PMR21ENAI (in the following referred to as ENAI), encoding an ATPase involved in sodium extrusion [4], and GPDI, encoding~a dehydrogenase involved in gljcerol synthesis [5]. Many other genes are also induced by saP, stress whose contribution to the adaptatio,a, if any, is not well understood [2].…”
mentioning
confidence: 99%